Analysis of Effective Strategies and Teacher Motivation in Improving Literacy and Numeracy at State Elementary School Besowo 5 Kediri: Findings and Implications: Analisis Strategi Efektif dan Motivasi Guru dalam Meningkatkan Literasi dan Numerasi di SDN Besowo 5 Kediri: Temuan dan Implikasinya - Afandi, 'Alia Nur Husna; Nafingah, Hanim; Pusnawati, Yeni; Triwahyuni, Yeni; Handayanto, Supriyono Koes; Kusumaningrum, Shirly Rizki (Pedagogia : Jurnal Pendidikan, 2024)
State Elementary School Besowo 5, Kepung District, Kediri, is an elementary school that succeeded in achieving high literacy and numeracy results on the education report card and achieved recognition as the Best BOSP Performance in Kediri Regency, even though the school experienced infrastructure challenges such as limited road access and limited cellular signal. The aim of this research is to explore the challenges, strategies and collaborative efforts of teachers in improving students' literacy and numeracy skills. The method in this research uses case studies through observation, interviews and document analysis. The analysis technique of this research uses triangulation techniques. Through the use of educational report cards as a basis, SDN Besowo 5 teachers provide special additional hours by utilizing a variety of literacy and numeracy materials, implementing various learning strategies, including guidance on finding keywords, Polya steps, using innovative worksheet, involving students as peer tutors, and provide treatment according to students' abilities. Apart from that, teachers also collaborate. Teachers' motivation for collaboration includes, among other things, improving school achievement, developing knowledge, and strengthening the school's positive image in the eyes of the community.